6-2x-1=4x+6-6x-3

Simple and best practice solution for 6-2x-1=4x+6-6x-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-2x-1=4x+6-6x-3 equation:


Simplifying
6 + -2x + -1 = 4x + 6 + -6x + -3

Reorder the terms:
6 + -1 + -2x = 4x + 6 + -6x + -3

Combine like terms: 6 + -1 = 5
5 + -2x = 4x + 6 + -6x + -3

Reorder the terms:
5 + -2x = 6 + -3 + 4x + -6x

Combine like terms: 6 + -3 = 3
5 + -2x = 3 + 4x + -6x

Combine like terms: 4x + -6x = -2x
5 + -2x = 3 + -2x

Add '2x' to each side of the equation.
5 + -2x + 2x = 3 + -2x + 2x

Combine like terms: -2x + 2x = 0
5 + 0 = 3 + -2x + 2x
5 = 3 + -2x + 2x

Combine like terms: -2x + 2x = 0
5 = 3 + 0
5 = 3

Solving
5 = 3

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| -(5b-1)=5b-(b-4) | | 7y^2-68y-20=0 | | -5-3(1-8p)=18-2p | | 2y-3x(x-8)=0 | | -103+2x=44-5x | | 232=-8(3x-5) | | 9x-9=18+6x | | 3+4y=15 | | 7-3r=r-(r+1) | | -2(3x-7)=36 | | 16+4x+3=-2x-(-6x)+12-(-7) | | 5x-100=-2x+40 | | 7x-4=-11x+6 | | 25x/45=-67 | | 1+7x=-5x-23 | | -4(1+k)=-3-3k | | (3y^2-8y+1)-(2y^2-8y+8)= | | -37-x=35-9x | | -3r-12=4-r | | x-7/6=2 | | X*4=100 | | 10n+5-8n-3=12 | | 2(m+3)= | | 9-5/8x=10 | | 12-15x(-5)= | | x^2+22x=-84+10x | | 7n+29=8 | | -12x^3+9x^2=0 | | -26+4= | | -4=a-10u | | 8+x=-(x+8) | | -5-10x^2=-68 |

Equations solver categories